Ocular fundus findings in Malawian children with cerebral malaria. - Lewallen, S; Taylor, T; Molyneux, M; Wills, B; Courtright, P (1993)
BACKGROUND: Cerebral malaria is a major cause of mortality and morbidity in children in tropical regions. The pathogenesis of this important complication of Plasmodium falciparum infection is not well understood. A number of observers have commented on the presence of retinal pathology in various types of malaria. Previous reports have not demonstrated that fundus findings are significantly associated with outcome. METHODS: The authors examined the ocular fundi, by direct and indirect ophthalmoscopy, of 56 children admitted consecutively with cerebral malaria. RESULTS: Every child with a normal fundus on admission recovered fully, but two conditions were found to be associated with a poor outcome. Patients with papilledema had a relative risk of poor outcome 5.2 times greater than those without this finding (P < 0.01). Patients with retinal edema outside the posterior vascular arcades had a relative risk of poor outcome 3.9 times greater than those without this finding (P < 0.01). These two fundus findings were independently predictive of a poor outcome. CONCLUSION: Fundus findings are useful as predictors of outcome in children with cerebral malaria. The authors' findings suggest that there may be two distinct mechanisms associated with poor outcome in these children.